Modulation of compositions and electrocatalytic activities of quaternary nanoporous Pt-based alloys via controllable dealloying. (15th June 2016) - Sun, Junzhe; Yan, Xuejiao; Zhao, Bingge; Liu, Lei; Gao, Yulai; Zhang, Zhonghua
Abstract: Electrocatalysts are crucial materials for applications of direct methanol fuel cells (DMFCs). Here, we have designed a novel multi-component nanoporous alloy electrocatalyst, and further modified its electrocatalytic performance through a controllable dealloying strategy. The quaternary nanoporous PtPdCuAl (np-PtPdCuAl) alloys have been successfully fabricated by dealloying mechanically alloyed AlCuPdPt precursor. Well control of one-step or two-step dealloying allows to tune the compositions and electrocatalytic activities of the np-PtPdCuAl alloys (designated as T1–T6 alloys). The np-PtPdCuAl alloys obtained through two-step dealloying show much enhanced electrocatalytic properties towards methanol electro-oxidation reaction (MOR) and oxygen reduction reaction (ORR) in comparison to the commercial benchmark Pt/C catalyst. Moreover, the np-PtPdCuAl alloy with the best MOR and ORR properties as well as excellent CO tolerance could be obtained by firstly dealloying in the 2 M NaOH solution and then in the 1 M HNO3 solution (T3 alloy). This facile synthesis and easy control route is promising for the development of high performance electrocatalysts in DMFCs, and can be extended to fabricate other multi-component Pt-based catalysts with enhanced activities. Graphical abstract: Highlights: Np-PtPdCuAl catalysts were fabricated by dealloying AlCu-based precursor powders. Nanoporous PtPdCuAl alloys show enhanced electrocatalytic properties for MOR and ORR. Electrocatalytic properties of np-PtPdCuAl can be modified by controllable dealloying.